2011
DOI: 10.1001/archgenpsychiatry.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Counseling During Brief and Extended Buprenorphine-Naloxone Treatment for Prescription Opioid Dependence

Abstract: Context No randomized trials have examined treatments for prescription opioid dependence, despite its increasing prevalence. Objective To evaluate the efficacy of brief and extended buprenorphine-naloxone treatment, with different counseling intensities, for patients dependent upon prescription opioids. Setting, Participants 653 treatment-seeking outpatients dependent on prescription opioids, at 10 U.S. sites from June 2006-July 2009. Design Multi-site, randomized clinical trial, using a two-phase adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
461
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(491 citation statements)
references
References 45 publications
26
461
1
3
Order By: Relevance
“…This fi nding supports previous reports indicating that heroin users are less likely to have successful treatment outcomes compared with OA users (Banta-Green et al, 2009;Brands et al, 2004;Moore et al, 2007). For example, one study found that any heroin use increased risk of poor treatment response compared with no heroin use in a sample that was primarily dependent on OAs (Weiss et al, 2011). As expected (Neufeld et al, 2008), injection status predicts poor treatment response to methadone and BUP treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This fi nding supports previous reports indicating that heroin users are less likely to have successful treatment outcomes compared with OA users (Banta-Green et al, 2009;Brands et al, 2004;Moore et al, 2007). For example, one study found that any heroin use increased risk of poor treatment response compared with no heroin use in a sample that was primarily dependent on OAs (Weiss et al, 2011). As expected (Neufeld et al, 2008), injection status predicts poor treatment response to methadone and BUP treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, injectors are less likely to complete treatment compared with non-injectors. These are particularly important fi ndings as retention in treatment is the best predictor of clinical outcomes (Corsi et al, 2009;Hutchinson et al, 2000;Weiss et al, 2011). Finally, as with opioid use at end of treatment, these results were irrespective of treatment assignment.…”
Section: Discussionmentioning
confidence: 91%
“…Although several studies showed that gradual outpatient buprenorphine tapers result in low rates of opioid abstinence (7–22% at 1 month),39, 40, 41 buprenorphine as maintenance therapy or for use in transition to other medications resulted in greater success. Patients treated with buprenorphine for the discontinuation of methadone or heroin exhibited milder withdrawal symptoms; therefore, buprenorphine gained acceptance as a medication that enabled easier transition onto naltrexone 23, 42, 43, 44, 45…”
Section: Historical Perspective On Clinical Management Of Opioid Withmentioning
confidence: 99%
“…3 Buprenorphine maintenance treatment of prescription opioid dependence is increasing in frequency and appears to be effective. 4 However, no data exist for buprenorphine maintenance treatment of addiction to fentanyl or sufentanil, the most common drugs of abuse among anesthesia personnel. 5 In addition, the role of buprenorphine maintenance treatment for such safety-sensitive specialties and professions has not been studied.…”
Section: W E Congratulate Mayo Clinic Proceedings and The Authors Hammentioning
confidence: 99%